Quantification of DOM effects on tetracyclines transport during struvite recovery from swine wastewater. (1st November 2021) - Huang, Xuewei; Ye, Zhi-Long; Cai, Jiasheng; Lin, Lifeng
Highlight: Sub-processes of DOM evolution for TCs transport in struvite recovery were examined. DOM underwent processes of hydrolysis, crystal adsorption and aggregation. Hydrolysis promoted TCs re-distributing among FDOM with various molecular weights. A distribution model was developed to describe TCs transport in struvite recovery. Abstract: Struvite (MgNH4 PO4 ·6H2 O) recovered from livestock wastewater may impose a pharmacological threat to the environment, due to the extensive existence of antibiotics in the wastewater. In this study, tetracyclines (TCs) were selected as the typical antibiotics, and the individual processes of dissolved organic matters (DOM) evolution and their effects on TCs migration in struvite recovery from swine wastewater were discriminated and quantified. Results revealed that TCs transport was contributed by the adsorption of pure struvite crystals, struvite adsorbing DOM-TCs complex and DOM aggregation, which occupied 2.29–6.53%, 23.53–34.66%, and 59.09–74.19% of the total TCs migration amounts, respectively. A tangential flow filtration system was employed to divide DOM into five fractional parts on the basis of molecular weight cut-offs. Experimental results indicated that under alkaline conditions of struvite crystallization, DOMs with larger molecular weights, hydrolyzed to DOMs with smaller molecular weights, which consequently promoted TCs re-distribution in DOMs from higher molecular weights to those with lower molecular weights. Furthermore, a distribution model was developed to characterize TCs transport in struvite recovery by describing TCs distribution among various phases, including struvite adsorption, DOM-TCs complexing, DOM aggregation, and free state in the solution, respectively. These outcomes provided new understanding on DOM evolution and effects on antibiotics transport in phosphate recovery from wastewater. Graphical abstract: Image, graphical abstract